Perlindungan Hukum Bagi Guru Dalam Menjalankan Fungsi Pendidikan Sebagai Upaya Mewujudkan Profesionalisme Pendidik - Sofyang Sofyang; Ahmad Riadi; Dandi Arya (Journal of Innovative and Creativity, 2025)
This study aims to analyze legal protection for teachers in carrying out educational functions as an effort to realize teacher professionalism. As professional personnel, teachers play a strategic role in educating the nation and shaping students’ character. In practice, teachers often face physical and psychological threats, criminalization, as well as administrative burdens that are disproportionate to their legal literacy. This study employs a normative legal research method with a juridical approach and literature review of legislation, books, and related journals. The results indicate that legal protection for teachers is divided into two forms: preventive, including rights guarantees, educational policies, and professional codes of ethics; and repressive, through legal advocacy, dispute resolution, and protection from criminalization. Effective legal protection provides legal certainty, creates a sense of security, strengthens teacher professionalism, and positively impacts the quality of education.